Open Problems in Extracellular RNA Data Analysis: Insights From an ERCC Online Workshop - Alexander, Roger P.; Kitchen, Robert R; Tosar, Juan Pablo; Roth, Matthew; Mestdagh, Pieter; Max, Klaas E. A.; Rozowsky, Joel; Kaczor-Urbanowicz, Karolina Elżbieta; Chang, Justin; Balaj, Leonora; Losic, Bojan; Van Nostrand, Eric L.; et al. (Frontiers in Genetics, 2022)
We now know RNA can survive the harsh environment of biofluids when encapsulated in vesicles or by associating with lipoproteins or RNA binding proteins. These extracellular RNA (exRNA) play a role in intercellular signaling, serve as biomarkers of disease, and form the basis of new strategies for disease treatment. The Extracellular RNA Communication Consortium (ERCC) hosted a two-day online workshop (April 19-20, 2021) on the unique challenges of exRNA data analysis. The goal was to foster an open dialog about best practices and discuss open problems in the field, focusing initially on small exRNA sequencing data. Video recordings of workshop presentations and discussions are available (https://exRNA.org/exRNAdata2021-videos/). There were three target audiences: experimentalists who generate exRNA sequencing data, computational and data scientists who work with those groups to analyze their data, and experimental and data scientists new to the field. Here we summarize issues explored during the workshop, including progress on an effort to develop an exRNA data analysis challenge to engage the community in solving some of these open problems.